Public Libraries in the Smart City - Leorke, Dale.; Wyatt, Danielle; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Pivot, 2019)
This book outlines the various ways in which public libraries have become entangled in visions of the 'smart city', where densely networked, ubiquitous connectivity promises urban prosperity built on efficiency, innovation and new avenues for civic participation. Drawing on theoretical analysis and interviews with library professionals, policymakers, and users, it examines the inevitable tensions emerging when a public institution dedicated to universal access to knowledge and a shared public culture intersects with the technology-driven, entrepreneurialist ideals of the smart city.
1. Introduction: More than Just a Library -- 2. Beacons of the Smart City -- 3. Mixed Metaphors: Between the Head and the Heart of the City -- 4. Metrics, Metrocentricity, and Governance Models: The Uneven Transformation of Public Libraries -- 5. Coda: Connection and Disconnection in a Digital Culture -- Index.
Keywords: Human geography; Library science; Sociology, Urban; Human Geography; Library Science; Urban Sociology